THE EFFECTIVITY OF SERVICE EXCELLENCE ON CUSTOMER SATISFACTION (STUDY CASE PT. PELABUHAN INDONESIA II (PERSERO) CABANG PANJANG) - Yani, Tri Evita; Agung, Maulana (Jurnal Kompetitif Bisnis, 2023)
Panjang in creating service excellence This study uses qualitative research methods that aim to determine the strategy of PT. Pelabuhan Indonesia II (Persero) Panjang Branch in creating service excellence which in its implementation is assisted by the Public Relations & Customer Service working group in the Panjang port commercial division. Data collection methods used are interviews, observations, and documentation studies. The results of this study found that Port of Panjang is actively launching a variety of customer-focused and customer-oriented programs. Some of the programs implemented to support this are through technology- based services, namely port digitization. The company continues to strive to improve its performance in order to maintain and improve its existence by implementing excellent service that is good and in accordance with company standards so as to create customer satisfaction.